Keefektifan Program Induksi Gutu Pemula (PIGP) di Kecamatan Bandar Kabupaten Batang - Nafia, Ilman; Siti Rodiyah; Nurkolis (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to evaluate the effectiveness of the Induction Program for New Teachers (PIGP) implemented in Bandar District, Batang Regency, Central Java. A qualitative research approach with a case study design was employed. The research subjects consisted of civil servant teachers participating in the PIGP program. Data were collected through observations, in-depth interviews, and document analysis. The findings reveal that implementing the PIGP program in Bandar District aligns with existing regulations, specifically the Regulation of the Minister of National Education No. 27 of 2010 and the Decree of the Director General of Islamic Education No. 5792 of 2019. The program has proven effective in supporting novice teachers in adapting to their professional environment and enhancing their pedagogical, professional, social, and personal competencies. This effectiveness is evident in the increased self-confidence and preparedness of teachers in fulfilling their professional responsibilities. Nevertheless, several challenges were identified, including insufficient training for mentors, the unavailability of comprehensive technical implementation guidelines, and limited outreach efforts by the local education authorities. To address these issues, it is recommended that the implementation quality be improved through ongoing professional development for mentors and the provision of detailed technical manuals.